Could Glyphosate and Glyphosate-Based Herbicides Be Associated With Increased Thyroid Diseases Worldwide? - Romano, Renata Marino; Oliveira, Jeane Maria de; Oliveira, Viviane Matoso de; Oliveira, Isabela Medeiros de; Torres, Yohandra Reyes; Bargi-Souza, Paula; Martino Andrade, Anderson Joel; Romano, Marco Aurelio (Frontiers in Endocrinology, 2021)
The increased incidence of thyroid diseases raises a series of questions about what the main predisposing factors are nowadays. If dietary restriction of iodine was once a major global health concern, today, the processes of industrialization of food and high exposure to a wide variety of environmental chemicals may be affecting, directly or indirectly, thyroid function. The homeostasis of hypothalamus-pituitary-thyroid (HPT) axis is finely regulated through the negative feedback mechanism exerted by thyroid hormones. Allostatic mechanisms are triggered to adjust the physiology of HPT axis in chronic conditions. Glyphosate and glyphosate-based herbicides are pesticides with controversial endocrine disrupting activities and only few studies have approached their effects on HPT axis and thyroid function. However, glyphosate has an electrophilic and nucleophilic zwitterion chemical structure that may affect the mechanisms involved in iodide oxidation and organification, as well as the oxidative phosphorylation in the ATP synthesis. Thus, in this review, we aimed to: (1) discuss the critical points in the regulation of HPT axis and thyroid hormones levels balance, which may be susceptible to the toxic action of glyphosate and glyphosate-based herbicides, correlating the molecular mechanisms involved in glyphosate toxicity described in the literature that may, directly or indirectly, be associated to the higher incidence of thyroid diseases; and (2) present the literature regarding glyphosate toxicity in HPT axis.